2019
DOI: 10.2147/tacg.s194166
|View full text |Cite
|
Sign up to set email alerts
|

<p>MTHFR C677T polymorphism and risk of nonsyndromic cleft lip with or without cleft palate in the Moroccan population</p>

Abstract: BackgroundNonsyndromic cleft lip with or without cleft palate (NSCL/P) is one of the most common craniofacial malformations observed. Several studies suggest that the decrease in folate has been associated with a higher risk of NSCL/P. The present study aimed to determine the association of 5,10-methylenetetrahydrofolate reductase (MTHFR) C677T polymorphism gene with the occurrence of NSCL/P in the Moroccan population.MethodsMTHFR C677T was genotyped in 52 Moroccan patients and 182 unrelated controls, using a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…In addition, TT + CT genotype was reported to have a significantly increased risk in five studies 34,39,44,46,52 and significantly decreased risk in four studies 36,47,55,57 in NSCL/P patients compared with controls. Based on the recessive model, three studies 39,46,54 reported significantly increased risk of TT genotype and one study 57 reported its significantly decreased risk in NSCL/P patients compared with controls.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In addition, TT + CT genotype was reported to have a significantly increased risk in five studies 34,39,44,46,52 and significantly decreased risk in four studies 36,47,55,57 in NSCL/P patients compared with controls. Based on the recessive model, three studies 39,46,54 reported significantly increased risk of TT genotype and one study 57 reported its significantly decreased risk in NSCL/P patients compared with controls.…”
Section: Discussionmentioning
confidence: 97%
“…Out of 31 studies included in the present meta-analysis, six studies 27,34,39,44,45,52 , five studies 34,39,44,46,52 , and four studies 34,39,46,52 reported significantly increased risk of T allele, TT genotype, and CT genotype in NSCL/P patients compared with controls, respectively. Also, five studies 36,47,49,55,57 , two studies 47,57 , and four studies 28,36,47,57 reported a significantly decreased risk of T allele, TT genotype and CT genotype in NSCL/P patients compared with controls, respectively. In addition, TT + CT genotype was reported to have a significantly increased risk in five studies 34,39,44,46,52 and significantly decreased risk in four studies 36,47,55,57 in NSCL/P patients compared with controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified 21 matches reporting the prevalence of MTHFR C677T and A1298C in various ethnic populations, and there were some differences in allele frequencies. For example, genotype CC at bp 677 is likely to be dominant in Moroccan patients ( 42 ) whereas genotype TT in 677 is dominant in Chinese patients and Iranian patients ( 43 , 44 ). Some ethnicities even showed higher frequencies of a functionally superior genotype of MTHFR C677T and A1298C in the patient groups, which is the opposite of our hypothesis.…”
Section: Discussionmentioning
confidence: 99%
“…Genotype and allele frequencies were calculated by genotype count[ 14 ] followed with test sample prediction by the assumption of Hardy–Weinberg (HW) equilibrium,[ 15 ] and both the control and cases were found to be in HW equilibrium. Statistical significance was accepted at P < 0.05.…”
Section: Methodsmentioning
confidence: 99%